Poly(3-hydroxybutyrate-CO-3-hydroxyvalerate) PHBHV biocompatible nanocarriers for 5-FU delivery targeting colorectal cancer - Ionut Cristian Radu; Ariana Hudita; Catalin Zaharia; Bianca Galateanu; Horia Iovu; Eugenia (Vasile); Sabina Georgiana Nitu; Octav Ginghina; Carolina Negrei; Aristidis Tsatsakis; Kelly Velonia; Mikhail Shtilman; et al. (Taylor & Francis Group, 2019)
Aiming to address the issue of poor bioavailability of most anti-tumor medicines against colorectal cancer, we developed a targeted anticancer nanocarrier using biocarriers able to both bind and easily release their load in a controlled manner. Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) carriers were obtained via the emulsification-diffusion method, loaded with 5-fluorouracil and then characterized in terms of particle morphology and size (SEM, DLS), drug uptake and release. The cytotoxic potential of the 5-fluorouracil-loaded polymer nanocarriers on human adenocarcinoma cells (HT-29 cell line) was investigated. The in vitro studies clearly demonstrated that while the nanocarriers themselves slightly alter HT-29 cell viability, when loaded with 5-fluorouracil they significantly decrease cell viability, suggesting that the polymer itself exhibits low cytotoxicity and the drug-loaded carrier acts in an efficient manner to kill HT-29 human adenocarcinoma cells.